The Polish Lexeme Węzłowaty and Its Russian Equivalents in the 17th and 18th Centuries - Николаев, Сергей (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper deals with three Russian translations of Bieniasz Budny’s book Krótkich a węzłowatych powieści, które po grecku zową Apoftegmata, księgi IV (1599), the research focusing on the problem of translating the word ‘węzłowaty’ from Polish into Russian. As many as seven different words were used to render this concept. The author considers these difficulties to be connected with the absence of a proper equivalent for the rhetorical concept ‘conceit’ (Lat. acutum) in Russian.